Analysis of theoretical model of innovation involvement in Educational Practice - Rozigul Umarova (Research Parks Publishing LLC, 2021)
Bringing the theoretical model of innovation as a system closer to educational practice is a criterion - the requirements for the introduction of a criterion of activity that allows to create an idea about the size and scope of innovation, the research conducted in this direction is analyzed